(untitled) - Sandfort, Jodi (San Francisco, 2015)
Effective Implementation in Practice: Integrating Public Policy and Management presents an instrumental approach to implementation analysis. By spanningpolicy fields, organizations, and frontline conditions in implementation systems, this book provides a robust foundation for policy makers, public and nonprofit managers and leaders. Detailed case studies enable readers to identify key intervention points, become more strategic, and improve outcomes. The engaging style and specific examples provide a bridge to practice, while diagrams, worksheets, and other tools included in the appendix help managers apply these ideas to team meetings, operational planning, and program assessment and refinement.
Keywords: Policy sciences,Quản trị công,Khoa học chính sách,Public administration; United States,Hoa Kỳ,Hoa Kỳ,United States